Volume Targeted Ventilation and High Frequency Ventilation as the Primary Modes of Respiratory Support for ELBW Babies: What Does the Evidence Say? - Ganguly, Abhrajit; Makkar, Abhishek; Sekar, Krishnamurthy (Frontiers in Pediatrics, 2020)
Respiratory management of the extremely low birth weight (ELBW) newborn has evolved over time. Although non-invasive ventilation is being increasingly used for respiratory support in these ELBW infants, invasive ventilation still remains the primary mode in this population. Current ventilators are microprocessor driven and have revolutionized the respiratory support for these neonates synchronizing the baby’s breath to ventilator breaths. High frequency ventilators with the delivery of tidal volumes less than the dead space have been introduced to minimize barotrauma and chronic lung disease. Despite these advances, the incidence of chronic lung disease has not decreased. There is still controversy regarding which mode is ideal as the primary mode of ventilation in ELBW infants. The most common modes seem to be pressure targeted conventional ventilation, volume targeted conventional ventilation and high frequency ventilation which includes high frequency oscillatory ventilation, high frequency jet ventilation and high frequency flow interrupter. In recent years, several randomized controlled trials and meta-analyses have compared volume versus pressure targeted ventilation and high frequency ventilation. While volume targeted ventilation and high frequency ventilation does show promise, substantial practice variability among different centers persists. In this review, we weighed the evidence for each mode and evaluated which modes show promise as the primary support of ventilation in ELBW babies.